Providing Hemodialysis in Unstable Areas: An Assessment and Framework for Effective Care - Sami Alasfar; Hani Alashavi; Khaled Hajj Nasan; Abd Aljabbar Haj Mousa; Camila Polinori; Valerie Luyckx; Mohamed Sekkarie; Saleh Kaysi; Lina Murad; Gilbert M. Burnham (Kidney International Reports)
Introduction: Providing hemodialysis to patients with kidney failure (KF) in conflict-affected areas poses a significant challenge. Achieving and sustaining reasonable quality hemodialysis operations in such regions necessitates a comprehensive approach. Methods: In the conflict area of Northwest (NW) Syria, a 3-phase project was initiated to address the quality of hemodialysis operations. The assessment phase involved the examination of infection prevention and control (IPC) protocols, staff training, medical protocols, individualized hemodialysis prescriptions, and laboratory testing capabilities. The second phase involved activities toward capacity building and implementing an action plan based on feasibility and sustainability. Results: The assessment phase revealed that only 7 of 14 centers had IPC protocols, and 8 centers provided IPC training for their staff. Furthermore, only 7 centers had medical protocols, and 5 used individualized hemodialysis prescriptions. Difficulties in testing for potassium was reported in 7 centers and the inability to perform hepatitis B and C serologies was reported in 3 centers. Only 2 centers adhered to machine and water treatment system maintenance guidelines, and 4 conducted daily water quality checks. Recommendations were formulated, and an action plan was developed for implementation in the second phase. The plan encompassed enhancements in IPC practices, medical protocols, record-keeping, laboratory testing, and equipment maintenance. Conclusion: This project underscores that hemodialysis services in conflict-affected areas do not meet the standards for quality care. It emphasizes the necessity of implementing a comprehensive framework that engages relevant stakeholders in defining and upholding quality care, a model that should be extended to other protracted conflict-affected regions.